Regular and Platform Switching: Bone Stress Analysis Varying Implant Type - Gurgel-Juarez, Nalia Cecilia; de Almeida, Erika Oliveira [UNESP]; Rocha, Eduardo Passos [UNESP]; Freitas Junior, Amilcar Chagas; Anchieta, Rodolfo Bruniera [UNESP]; Mercon de Vargas, Luis Carlos; Kina, Sidney; Gomes Franca, Fabiana Mantovani (Wiley-Blackwell, 2012)
Purpose: This study aimed to evaluate stress distribution on peri-implant bone simulating the influence of platform switching in external and internal hexagon implants using three-dimensional finite element analysis.Materials and Methods: Four mathematical models of a central incisor supported by an implant were created: External Regular model (ER) with 5.0 mm x 11.5 mm external hexagon implant and 5.0 mm abutment (0% abutment shifting), Internal Regular model (IR) with 4.5 mm x 11.5 mm internal hexagon implant and 4.5 mm abutment (0% abutment shifting), External Switching model (ES) with 5.0 mm x 11.5 mm external hexagon implant and 4.1 mm abutment (18% abutment shifting), and Internal Switching model (IS) with 4.5 mm x 11.5 mm internal hexagon implant and 3.8 mm abutment (15% abutment shifting). The models were created by SolidWorks software. The numerical analysis was performed using ANSYS Workbench. Oblique forces (100 N) were applied to the palatal surface of the central incisor. The maximum (sigma(max)) and minimum (sigma(min)) principal stress, equivalent von Mises stress (sigma(vM)), and maximum principal elastic strain (epsilon(max)) values were evaluated for the cortical and trabecular bone.Results: For cortical bone, the highest stress values (sigma(max) and sigma(vm)) (MPa) were observed in IR (87.4 and 82.3), followed by IS (83.3 and 72.4), ER (82 and 65.1), and ES (56.7 and 51.6). For epsilon(max), IR showed the highest stress (5.46e-003), followed by IS (5.23e-003), ER (5.22e-003), and ES (3.67e-003). For the trabecular bone, the highest stress values (sigma(max)) (MPa) were observed in ER (12.5), followed by IS (12), ES (11.9), and IR (4.95). For sigma(vM), the highest stress values (MPa) were observed in IS (9.65), followed by ER (9.3), ES (8.61), and IR (5.62). For epsilon(max), ER showed the highest stress (5.5e-003), followed by ES (5.43e-003), IS (3.75e-003), and IR (3.15e-003).Conclusion: The influence of platform switching was more evident for cortical bone than for trabecular bone, mainly for the external hexagon implants. In addition, the external hexagon implants showed less stress concentration in the regular and switching platforms in comparison to the internal hexagon implants.
Keywords: Implant dentistry; finite element analysis; bone; stress; loading